2015
DOI: 10.1021/jacs.5b01543
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Phosphorylcholine Derivatives of Poly(serine) and Poly(homoserine)

Abstract: ABSTRACT:We report methods for the synthesis of polypeptides that are fully functionalized with desirable phosphorylcholine, PC, groups. Due to inherent challenges in the direct incorporation of the PC group into α-amino acid N-carboxyanhydride (NCA) monomers, we developed a synthetic approach that combined functional NCA polymerization with efficient postpolymerization modification. While poly(L-phosphorylcholine serine) was found to be unstable upon synthesis, we successfully prepared poly(L-phosphorylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…55 The bromoethyl functionalities were stable during (PMe 3 ) 4 Co mediated polymerization in THF, and Chem. Rev.…”
Section: Azido Modified Ncasmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The bromoethyl functionalities were stable during (PMe 3 ) 4 Co mediated polymerization in THF, and Chem. Rev.…”
Section: Azido Modified Ncasmentioning
confidence: 99%
“…76 Deming's lab also used alkyl bromide functionalized phosphoryl serine and homoserine polymers in a PPM reaction with trimethyl amine to generate the first example of phosphorylcholine modified polypeptides ( Figure 22D). 55 These polypeptides possess side-chain groups that mimic the functionalities of phosphorylcholine containing lipids. Due to its zwitterionic nature, this polypeptide was found to possess a disordered conformation in water at pH ranging from 3.0 to 11.…”
Section: Other Reactionsmentioning
confidence: 99%
“…Amino acids are naturally available renewable resources, and recent advances in aerobic fermentation have made it possible to obtain amino‐acids with high purity and relatively low price. Therefore, extensive research has focused on the synthesis of biorenewable polymers based on amino‐acids monomers . We previously proposed a new chemical strategy based on ring‐opening polymerization (ROP) to obtain ε ‐poly‐lysine from lysine .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that PGA forms an α‐helical structure under aqueous conditions at ambient temperatures . Studies reporting homo serine polymers are rare and typically use serine derivatives (e.g., phosphorylcholine side groups) instead to improve water solubility and control chain length distribution . While there are no examples in the literature of copolymers of glutamic acid and serine synthesized by ROP, a similar system, a random copolymer of L‐serine and N‐(4‐hydroxybutyl)‐glutamine, was reported to undergo a thermally induced helix–coil transition.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,20 Studies reporting homo serine polymers are rare and typically use serine derivatives (e.g., phosphorylcholine side groups) instead to improve water solubility and control chain length distribution. 21 While there are no examples in the literature of copolymers of glutamic acid and serine synthesized by ROP, a similar system, a random copolymer of L-serine and N-(4-hydroxybutyl)-glutamine, was reported to undergo a thermally induced helix-coil transition. Using circular dichroism, it was shown that serine acts as an a-helical breaker and participates in b-turns, 22 but the effect of copolymer composition was not explored.…”
mentioning
confidence: 99%